Joint Production Committee, 1942 (United Kingdom, 1942)
1942 1939-1945 "Joint Production Committee, 1942" [HFR0035], 1942 A Joint Production Committee in a large Royal Ordnance Factory. Workers and management were encouraged to form Joint Production Committees to discuss efficiency, output and sometimes piece rates and bonuses. By the end of 1943, over 4000 Joint Works Production Committees had been established in the engineering and shipbuilding industries to resolve any issues arising from the Essential Works Orders which might disrupt production.